(untitled) (Al-Academy, 2020)
The rapid changes in the field of transferring and exchanging information via cloud platforms have revolutionized the field of modern visual media, as cloud computing technology has greatly influenced the media institutions, providing effort, money and high-quality materials. The research included five chapters, the first came under the methodological framework for the research and the second Theoretical framework, the first two included the concept of cloud computing and the second platforms for cloud computing in the visual media and the third chapter Research procedures and the fourth chapter The sample analysis and the fifth chapter The research results were the most prominent1. The cloud service made the benefit beyond the typical and traditional in the media work and speed in accomplishing it.2. High picture and sound quality, with the ability to make montages on it before transferring to the beneficiary3. Low costs, as it became possible to dispense with many old broadcast and reception machines.With a list of sources and search references